2020
DOI: 10.1177/0896860819879596
|View full text |Cite
|
Sign up to set email alerts
|

Tension-free mesh repair of inguinal hernia in patients on continuous ambulatory peritoneal dialysis

Abstract: Background: Peritoneal dialysis (PD) is the first-line renal replacement therapy for end-stage renal failure patients in Hong Kong. Abdominal wall hernia is a common mechanical complication of PD, and early surgical repair has been advocated to reduce complications. This study aims to review the outcomes of tension-free mesh repair of inguinal hernia in PD patients. Methods: All PD patients who underwent elective repair of inguinal hernia from 2009 to 2015 were identified from a single centre for retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
(38 reference statements)
4
10
0
5
Order By: Relevance
“…In addition, due to the frequent infusion of peritoneal dialysis and the presence of prostheses as foreign bodies, infectious complications are likely to occur, particularly if the sterile technique needed for hernioplasty is not strict enough. We did not observe any wound or mesh infection in our group of patients after treatment with antibiotic prophylaxis, which was consistent with the ndings of other studies [6,9]. Although there were two patients in our study who developed bacterial peritonitis 2 and 3 months after hernioplasty, considering the time interval between surgery and infection, we believe that the infection was not related to surgery, as observed in the other studies [6,10]; moreover, both patients were cured after intraperitoneal antibiotic treatment without removal of the peritoneal catheter or interruption of CAPD.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In addition, due to the frequent infusion of peritoneal dialysis and the presence of prostheses as foreign bodies, infectious complications are likely to occur, particularly if the sterile technique needed for hernioplasty is not strict enough. We did not observe any wound or mesh infection in our group of patients after treatment with antibiotic prophylaxis, which was consistent with the ndings of other studies [6,9]. Although there were two patients in our study who developed bacterial peritonitis 2 and 3 months after hernioplasty, considering the time interval between surgery and infection, we believe that the infection was not related to surgery, as observed in the other studies [6,10]; moreover, both patients were cured after intraperitoneal antibiotic treatment without removal of the peritoneal catheter or interruption of CAPD.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found no recurrences after tension-free mesh repair for inguinal hernia, including those patients who had early resumption of CAPD after repair, which demonstrates that tension-free mesh hernioplasty for CAPD patients is safe and feasible, which is consistent with the ndings of other studies [5,6,9,10]. Luk et al [6] demonstrated that the Lichtenstein mesh repair remains the gold standard for patients with CAPD. Gianetta et al [10] also claimed that the results of the Lichtenstein technique under local anesthesia for these high-risk subgroups are satisfactory.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations